SOIL AND SUGAR QUALITY IMPROVEMENT INFLUENCED BY MULCHING AND WEED MANAGEMENT PRACTICES IN NIGERIA - Moses Samuel BASSEY; Emmanuel Abraham SHITTU; Ekaette Eunice ETIM; Ekaette Joy ETOPOBONG (Journal of Plant Development)
Yield decline is an issue that has plagued sugarcane production in Nigeria. The objective of the study was to evaluate the effects of sugarcane trash mulch and weed management practices on soil C and N, and sugar quality production. The treatments consisted of factorial combination of two sugarcane genotypes (Bida local and NCS 001), four sugarcane trash mulching levels (0, 3, 6, 9 t ha-1) and four weed management practices: weedy check, 5 monthly hoe weeding (5MHW), pre-emergence (PE) application of diuron at 2 kg a.i./ha + Post-Emergence (POE) of 3-Maize force at 179.2 g/ha + Two hoe weeding (2HW), and PE Diuron + POE 3-Maize force arranged in a split plot design and replicated three times. The results showed that application of 9 t ha-1 trash mulch significantly (P<0.05) produced the highest organic carbon, N, which in turn enhanced sugar yield. Similarly, the application of 9 t ha-1 trash mulch plus PE+POE produced the highest NCS 001 sugar quality. Application of trash mulching at 9 t ha-1 plus PE+POE effectively enhanced soil C and N, and sustained the productivity of NCS 001 sugar quality in the study area and related ecologies.